THE MAIN DIRECTIONS FOR PHARMACOLOGICAL CORRECTION (COMBINATIONS OF DRUGS FOR GENERAL ANESTHESIA) OF NEUROLOGICAL AND COGNITIVE DISORDERS IN PATIENTS WITH NEOPLASMS OF THE CENTRAL NERVOUS SYSTEM - Andrey Kolesnikov; Georgiy Gorodnik; Aleksandr Grigorenko; Timur Mustafin; Nikolai Kolesnikov; Igor Koktishev (Belgorod National Research University, 2017)
Introduction: the problem of neuroprotective or neurodegenerative effects of drugs for general anesthesia is relevant in connection with a large number of cases of postoperative cognitive dysfunction (POCD). Objectives: the aim of the study was to develop a goal-oriented combination of drugs for general anesthesia, based on a retrospective assessment of the baseline level of neurological and cognitive disorders in adults and children at the stage of preparation for surgery for neoplasms of the central nervous system (sub- and supratentorial neoplasms - SubTNN and SupraTNN), and a prospective evaluation of complications in the postoperative period. Methods: an experimental prospective multicenter open-label study. Criteria for including patients in the study. Patients over 5 years divided into subgroups of children (5-17 years) and adults (over 18 years), with neoplasms of the CNS, with indications for surgical treatment (operation: total or subtotal neoplasm removal). We examined 303 adult patients and 125 children who underwent surgery for CNS neoplasms of different localization. Results: а special feature in the initial assessment of the severity of patients with ICP tumor origin is the relationship not only with neurological deficits (GCS 11.0 ± 3.0 points, MMSE 23.0 ± 2.2 points, MRC 3.2 ± 1.1 points), but with multiple organ damage according to the SOFA scale (up to 4-5 systems, with an estimate of 12.0 ± 3.5 points). The constant intraoperative risks associated with ICP syndrome include: a chance of developing hemodynamic instability in adults from 32.1 to 32.7% for SubTNN, in children up to 30% for SubTNN. Characteristics of the dynamics of neurospecific proteins were first isolated depending on the indicators of central and cerebral dynamics in children and adults with neoplasms of the central nervous system. Disturbance of cerebral hemodynamics and the presence of the main pathology (neoplasms of the posterior cranial fossa - PCF) in patients of the SubTNN group caused an increase in the value of the S-100 protein. The mean values were 0.239 ± 0.13 μg/ml, Me = 0.179 (0.171-0.19) in adults and 0.251 ± 0.093, Me = 0.16 (0.12-0.2) in children, which was higher than normal. When assessing the degree of neuroregeneration by the level of the CNTF value, it was revealed that the mean values were significantly increased in the subgroups of adults and children, and amounted to 17.64 ± 7.92 pg/ml, Me = 11.63 (9.37-12.26) in adults, and 12.9 ± 0.71, Me = 11.35 (8.46-12.18) in children. In the SupraTNN group, the elevated levels of the average S-100 protein values up to 0.266 ± 0.043 μg/ml, Me = 0.148 (0.129-0.145) were found in adults, and up to 0.225 ± 0.04 μg/ml, Me = 0.135 (0.092-0.165) in children. The degree of neurodegenerative processes, due to the supratentorial neoplasm, was high in both children and adults. At the same time, mean values of the level of CNTF in this group were significantly higher than in all comparison groups and amounted to 27.09 ± 11.5 pg/ml, Me = 17.76 (14.55-20.7) in adults, and 26.24 ± 5.06 pg/ml, Me = 14.56 (12.04-15.84) in children. Multicomponent modifications of general anesthesia for patients with neoplasms of the central nervous system aimed at correction and prevention of neuro-cognitive impairment by the influence on the links of the stress system have been developed. To stimulate the stress-limiting (SL) link, benzodiazepines, sodium oxybutyrate are used, barbiturates, inhalation anesthetics are used to stimulate the stress-limiting link and inhibit the stress-activating (SA) link, ketamine is used to stimulate the stress-activating link, clonidine is used for simultaneous stimulation of the stress-activating and stress-limiting link, and fentanyl is used for simultaneous suppression of stress-activating and stress-limiting elements. Conclusion: The revealed age-specific features of neuro-cognitive deficits in patients with neoplasms of the central nervous system indicate the need for an individual pharmacological approach to the combination of drugs for general anesthesia, with an aim to reduce postoperative deficits.